Implementation of a Puzzle Educational Game Based on Liveworksheet in Learning Science through the PAIKEM Method for Class VI - Nisa' Faaiqoh; Ika Ratnaningrum (Postgraduate, University of Mataram, 2024)
This study aims to describe the implementation of educational puzzle games based on Liveworksheet in teaching IPAS through the PAIKEM method in the sixth grade of SD Negeri Gunung Pati 01. The research method used in this study is descriptive qualitative. The data obtained from this research were collected through interviews, observations, and documentation. The data analysis technique employed in this research follows the Miles & Huberman approach, which includes data collection, data reduction, data display, and verification. Based on the results of the study, it can be concluded that the implementation of educational puzzle games based on Liveworksheet in IPAS teaching through the PAIKEM method in the sixth grade of SD Negeri Gunung Pati 01, Semarang City, has a significant impact on the IPAS learning process. The implementation of the liveworksheet-based educational puzzle game in IPAS learning for sixth-grade students at SD Negeri Gunung Pati 01 can be observed from the students' enthusiasm in participating in learning activities. Students became more active, their understanding of the learning material increased, and their interest in learning improved due to the use of the liveworksheet-based educational puzzle game. This media also helps develop students' critical thinking and problem-solving skills.